2016
DOI: 10.23910/ijbsm/2016.7.1.1480
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth and Productivity of Wheat, Chickpea and Potato as Influenced by Nutrient Management Practices

Abstract: Field experiments were conducted during rabi / winter (November-March) seasons of 2011-12 and 2012-13 at research farm of Indian Agricultural Research Institute, New Delhi to evaluate the root growth and performance of wheat, chickpea and potato grown in different soybean-based cropping systems with 5 nutrient management practices. The results revealed that root growth in terms of root length, root volume and root dry weight of wheat and chickpea were observed significantly maximum where 50% RDN was substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…with unsustainability issue in agriculture. Indiscriminate and continuous use of inorganic fertilizers has shown negative effect on physico-chemical and biological properties of soil, thereby affecting the crop productivity (Prajapat et al, 2016;Meena et al, 2018), besides causing environmental pollution (Virmani, 1994). The excessive use of pesticides also resulted in residues much above the safety levels and this brought to the attention of ill-effects of modern agriculture and paved the way for organic based farming which will not only give rich nutrients produce but also quality food devoid of any chemical residue (Mengi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…with unsustainability issue in agriculture. Indiscriminate and continuous use of inorganic fertilizers has shown negative effect on physico-chemical and biological properties of soil, thereby affecting the crop productivity (Prajapat et al, 2016;Meena et al, 2018), besides causing environmental pollution (Virmani, 1994). The excessive use of pesticides also resulted in residues much above the safety levels and this brought to the attention of ill-effects of modern agriculture and paved the way for organic based farming which will not only give rich nutrients produce but also quality food devoid of any chemical residue (Mengi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact structure can only be determined by laboratory analysis. In general, the nutritional quality of maize increases with the use of feed with a combination of organic and inorganic fertilizers [7]. Prajapati et al [7], from their research, reported that the highest nutrient uptake of N, P 2 O 5, and K 2 O was observed under treatment where integration of organic and inorganic source is applied i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the nutritional quality of maize increases with the use of feed with a combination of organic and inorganic fertilizers [7]. Prajapati et al [7], from their research, reported that the highest nutrient uptake of N, P 2 O 5, and K 2 O was observed under treatment where integration of organic and inorganic source is applied i.e. 25% RDF + 50% FYM + Biofertilizer over sole application of either organic or inorganic material.…”
Section: Resultsmentioning
confidence: 99%
“…This results indicated that higher average grain yield in demonstration plots compare to farmers' practice ascribed to the knowledge and adoption of improved technologies i. e. suitable high yielding varieties with more potential yield such as GNG-469 and GNG-663, timely sowing, seed treatment with fungicides and biofertilizers (Rhizobium PSB culture), use of balanced fertilization, timely weed management and need based plant protection measures. Prajapat et al (2016) yield enhancement, greater yield attributing characters and better root traits of chickpea due to application of recommended dose of fertilizers and biofertilizers. Likewise, yield enhancement in different chickpea varieties ascribed to phosphorus addition in vertisols (Neenu et al, 2014).…”
Section: Chickpea Yieldmentioning
confidence: 99%